Fired and Pregnant: Gender Differences in Job Flexibility Outcomes after Job Loss - Jordy Meekes; Wolter Hassink (Institute of Labor Economics (IZA), 2020)
We study whether women and men cope with job loss differently. We use 2006-2017 Dutch administrative monthly microdata and a quasi-experimental design involving job displacement because of firm bankruptcy. We find that displaced women are more likely than displaced men to take up a flexible job with limited working hours and short commutes. However, displaced women experience longer unemployment durations and comparable hourly wage losses. Displaced expectant mothers experience relatively high losses in employment and working hours. Our findings suggest that the costs of job flexibility for displaced female workers come through longer unemployment instead of higher losses in wages.
Keywords: J16; J22; J31; J32; J6; R2; 330; job loss; gender; job flexibility; working hours; commute; household; pregnancy